Polymer based micro-fluidic devices : improvement in thermal bond strength of COC micofluidic device using photografting technique - Tan, Hsien Tat. (2011)
In recent times, Microfluidic devices have gained substantially high interest in both industrial and academic research due to the key advantages demonstrated by the device to achieve fast response time and low analyte consumption required for testing. This project reports on the development and application of a permanent surface modification technique in photografting as an improved method for bonding TOPAS@COC microfluidic substrates with a cover plate without affecting the channel integrity. Photografting technique aids in increasing the bond strength of the modified surface as well as enhancing quick flow when analyte is being passed through the device by making the surface more hydrophilic. This project serves to improve the bond strength by modifying the surface of the polymer using photografting technique while evaluations of the modified surfaces were done through using Fourier transform infrared spectroscopy (FTIR), contact angle measurement, X-ray photoelectron spectroscopy (XPS) and the surface roughness with the atomic force microscope (AFM).